Circulation pattern on the old building of Bandung Elektronik Center - Widia Wati; Salmon Priaji Martana (Jurnal Arsitektur Archicentre, 2023)
A shopping center must have a good circulation pattern to provide visitors with the convenience to access the building in and out. This study aims to determine the pattern of visitor circulation in the Bandung Elektronik Center building, in relation mainly to the placement of entrances and exits. The method is descriptive analysis, through surveys of the circulation inside the building. As a result, the building circulation can be improved by redesigning the visitor circulation system, paying more attention to the visitor's convenience in accessing every part of the environment.